Instagram use and online subjective well-being among early adulthood: The mediating role of information gratification - Su'ad Jauharoh; Maratul Jannah Umbola; Shofiya Mar'ah; Zulfa Auna (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Previous studies have mainly emphasized the negative impacts of social media and focused on affective and social mechanisms, while cognitive mechanisms like information gratification remain underexplored. This study examined the role of information gratification as a mediator between Instagram use and online subjective well-being among early adult college students. Using a survey design, data were collected from 142 college students aged 18–25 years through the Instagram Use Scale, Information Satisfaction Scale, and Online Subjective Well-being Scale, and analyzed using mediation analysis in JASP. Results showed that Instagram use positively affects online subjective well-being (β = 0.248, p = 0.002) and information gratification (β = 0.594, p < 0.001). Information gratification was also found to positively affect online subjective well-being (β = 0.431, p < 0.001) and partially mediates the relationship between Instagram use and online subjective well-being (β = 0.256, p < 0.001). These findings highlight the importance of cognitive mechanisms in understanding the psychological benefits of Instagram use.